SUSTAINABLE MIDWIFE CARE MANAGEMENT (Continuity Of Care) AT NY.N WITH GRADE II PERINEUM RUPTURE AT PMB AZRI YANI KEC.DELI TUA KAB.DELI SERDANG FIELD CITY IN 2024: SUSTAINABLE MIDWIFE CARE MANAGEMENT (Continuity Of Care) AT NY.N WITH GRADE II PERINEUM RUPTURE AT PMB AZRI YANI KEC.DELI TUA KAB.DELI SERDANG FIELD CITY IN 2024 - Yesica Simbolon; Eva Ratna Dewi; Marliani; Ribur Sinaga; Ade Rachmat Yudiyanto; Damayanty (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Background : According to WHO in 2019, the maternal mortality rate (MMR) in the world is 303,000, the maternal mortality rate (MMR) in ASEAN is 235 per 100,000 live births. According to the Indonesian Demographic and Health Survey Data, the Maternal Mortality Rate (MMR) is 305 per 100,000 live births and the Infant Mortality Rate is 24 per 1000 live births. The number of maternal deaths in Indonesia in 2020 was 4,627 deaths and in 2021 the number of maternal deaths increased by 7,389 deaths. Based on the data obtained in North Sumatra, the maternal mortality rate is 119 cases for infant mortality is 299 cases. To reduce MMR and IMR, midwifery care management can be carried out to solve problems from assessment, identification of problems and needs, anticipation of potential problems, immediate action, planning, implementation, and evaluation. In addition, Continiuty Of Care (COC) is an effort to provide continuous care starting from pregnancy, childbirth, postpartum, newborn and family planning. This care aims to monitor the condition of mothers and babies as an effort to reduce maternal mortality rates (MMR) and infant mortality rates (IMR) Methodology : The type used is a case study or Case Study, which is an observational study to obtain an overview of health phenomena or current cases related to life, especially in context boundaries and phenomena that are not clear. Results : From the results of research conducted during pregnancy, childbirth, newborn, postpartum to family planning, there were no gaps in the provision of care. Conclusion : Midwifery care is carried out to overcome the patient’s complaints, namely pain in the waist by providing health services, by encouraging the mother to have adequate rest patterns by resting when feeling tired, encouraging the mother to take a 1-2 hour nap and 7-8 hours of sleep at night and to reduce activities that are too heavy, during the postpartum period and after the postpartum period the mother did not experience any complaints, all normal, there were no complications during the postpartum period. Monitoring of newborns is also done to find out if there are abnormalities in the baby. the use of maternal contraceptives with the MAL method.